Coworking Space Planning and Design : Mixed Use Building With A Tropical Architectural Approach - Muhammad Aly Mujahidin; Cut Nuraini; Benny Iskandar (International Forum of Researchers and Lecturers, 2022)
The impact of covid 19 makes the habits of people who work and students often work or study via online. A cozy and adequate space is needed to carry out online activities and freelance work. The right solution is to design a coworking space mix use building that can provide space and facilities to support comfort for consumers. Coworking Space is a workspace concept that can be used together with various backgrounds such as students, freelancers, students, entrepreneurs, or other companies. In Medan City coworking spaces are still relatively few that have multi-functions as the author designs. Most only prioritize one function so that consumers can easily get bored when working. In this design, hopefully it can be a problem solver and become a comfortable working, meeting and relaxing space for consumers.